CREATION OF INSTITUTIONAL ENVIRONMENT OF DIGITAL ECONOMY IN RUSSIA (Revista Inclusiones, 2020)
The problem in question is relevant since formation of digital economy is progressing rapidly in Russia and throughout the world. It not only drastically changes man’s life but changes the structure of institutional environment. On the other hand, development of digital economy can occur only in conditions of appropriate institutional environment. The objective of the paper is to make institutional environment of digital economy, the subject of this paper, a standalone scientific area, and to identify whether a degree of institutional environment created in Russia is in line with that of the formed digital economy and its integration into digital environment of the other countries’ economy.